Making it modern : the history of Modernism in architecture and design - Betsky, Aaron (New York : Actar Publishers, 2016)
b
What modern is: introduction -- Space opens up -- Staging modernity: the aesthetics of the future -- A new style of life: artifacts of modernity -- At home in the brave new world -- Buildings like crystals, forms as cold ice: the styling of modernity -- Toward totality: planning for perfection -- The human form endures: contingent modernism -- Wooden ships: the modernism of complexity and contradiction -- After modernism: experimental design -- Re-modernism: design for sprawl.
Includes bibliographical references (pages 335-344) and index.
E-book.
Keywords: Modern movement (Architecture); Politics & Economics